Implementation of Giving Date Juice to Increase Hemoglobin Levels in Patients with Anemia - Masluh Aziz, Iman; Hamdani, Dadi (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Anemia is a disease characterized by a lack of red blood cells in the blood or what can be called hemoglobin (HB) levels in the blood that are lower than normal values. The diagnosis of anemia can be made if the hemoglobin level is <12g/dl in women and <13g/dl in men. Objective: This study was conducted to present the intervention of giving date palm juice to increase hemoglobin levels in anemia patients. Method: The reseach design used by the author is a case study with a nursing approach where this research was carried out by collecting data starting from assessment, diagnosis, planning, implementation of activities and implementation of focused assessment. In this case study, a descriptive method was used with the main aim of problem exploration and an indepth analysis of anemia nursing was carried out to provide an overview of the case study. Result: The nursing diagnosis of ineffective peripheral tissue perfusion is related to decreased HB. The intervention of giving date palm juice was given for 10 days with 3 tablespoons a day. After the intervention was carried out, the nursing problem of ineffective peripheral tissue perfusion for the client was resolved, indicated by the HB value which was originally below the normal range. with an HB value of 10.8 gr/dl. After being given intervention, it increased to the normal range with HB results of 11.8 gr/dl. Conclusion: Giving date juice has proven to be useful in increasing Hemoglobin level.